Information Technological System for Maxillofacial Area Bones Prototyping - Sorokovyi, Oleksandr; Golovko, Gennady; Dmytrenko, Tatyana; Derkach, Tatyana (International Journal of Engineering and Technology, 2018)
The research is devoted to the sequential movement of digital information between different software products, eliminating at each stage the problems of conversion, recognition, fine-tune the parameters of operations, that is, the development of a kind of technological map of the process of obtaining a material model of a part of a human skeleton for use in maxillofacial surgery. An information technology system for obtaining 3D models of the lower jaw bones with the use of tomography and free CAD/CAM InVesalius 3 and Autodesk software is developed. InVesalius 3 software was used to provide semi-automatic image segmentation using the Hounsfield scale and build a specific three-dimensional voxel model, based on the virtual layered individual images combination. Voxel models convert to STL file and editing surface «artifacts» (inaccuracies) with Autodesk, MeshMixer.  Completed prototyping bone and implant models obtained on a FDM 3D printer are used in maxillofacial surgery.
Keywords: Autodesk MeshMixer; CAD/CAM; software information technology system; InVesalius 3; prototyping.